Enrique the Slave Dreams from Seville and other Poems - Javier, Jeffrey B. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 01 (2022): LIKHAAN 16: The Journal of Contemporary Philippine Literature, 2023)
The poems appeal to the idea of nostos or the homeward journey to an originary locus that is not accessible anymore. They anticipate the longing for a home—to which, in the end, one could no longer return.